LCC hypothesis in the context of environmental taxes, renewable energy, and trade flow in Romania - Magdalena Radulescu; Mirela Panait; Kamel Si Mohammed; Hind Alofaysan; Syed Ale Raza Shah; Bogdan Marza (Energy Exploration & Exploitation)
This study investigates the role of environmental regulations, renewable energy, and the validity of the load capacity curve (LCC) hypothesis. The natural environment offers a range of ecosystem services; however, it is important to recognize that these services have finite limits, and overuse can result in a biocapacity deficit. To restore biocapacity, it is essential to prioritize renewable energy, enforce stricter environmental taxation, and closely monitor trade flows. This paper first assesses Romania's LCC hypothesis by considering the impact of environmental taxes, renewable energy, and trade. Utilizing data from the first quarter of 1994 to the fourth quarter of 2022, the study employs method of moments quantile regression and quantile regression techniques to derive its empirical findings. The results confirm the validity of the LCC hypothesis and highlight the significant influence of trade and renewable energy on the load capacity factor. These findings offer valuable insights for Romanian policymakers, suggesting that adopting renewable energy and environmental taxes can mitigate trade's ecological and socioeconomic impacts without hindering economic growth and the pursuit of sustainable development goals. The authors also propose new policy recommendations to align sustainable energy use with economic objectives.